Efeito do ponto de orvalho da atmosfera protetora dos fornos de recozimento contínuo na qualidade do revestimento Galvannealed - Juliana Porto Guimarães (2012)
The strip steel surface condition after continuous annealing of stri p is extremely important to the qual ity of the coatings obtained in the hot dip galvanizi ng. The presence of oxides or segregated elements on the sirface of the annealed material can affect the reactions at the coating/substrate interface and the zinc wettability on the steel surface, leading to various defects in the final product. Thus a protective atmosphere is used in the continuous annealing furnaces in order toreduce the iron oxides present on the steel surface. Despite the protective atmosphere it is po$i ble the occurrence of selective oxidation and precipitation of second phw particles on the steel surface during continuous annealing, bei ng the dew point of atmosphere is one of the main factors to be considered to reduce this occurrence. Therefore, this study aimed to evaluate the effect of the dew point of the anneaing atmosphere on the qua ity of gal vanneaed coating (GA) applied to two types of steel: (i) ultra low carbon steel with bake hardenability characteristics, yield strength of 21OMPa, called BH210; and (ii) dual ph& steel, yield drength of 800MPa, called DP800. The continuous arineding simulation of these steels under protective atmosphere with different dew points, as well as hot dip galvanizing, were performed in a hot dip process simulator (HDPS). The selective oxidation on the surface of anneded steel was evaluated by X ray photoel ectron spectroscopy (XPS), scanning electron microscopy with field emission gun and enagy-dispersi ve X-ray spectroscopy coupled (FEG-SEM/EDS) and glow discharge optical emission spectroscopy (GDOES). The coatings were characterized using SEIVI/EDS, X ray diffraction (XRD), inductively coupled plasma atomic emision spectroscopy (ICP/AES) and adhesion test. The results showed that the dew point of the protective atmosphere of continuous annealing furnaces has a decisive influence on the amount, distribution and type of oxides formed on the surface of evaluated steels. For BH21O steel, the employment of the dew point of -30°C during anneding provided coatings with the best qudity, while for the DPBOO Qeel protective atmospheres with dew points between -30°C and 60°C provided coatings with less fdluros and better adhesion.